Oral Administration of Lactobacillus plantarum Strain AYA Enhances IgA Secretion and Provides Survival Protection against Influenza Virus Infection in Mice - Kikuchi, Yosuke; Kunitoh-Asari, Ayami; Hayakawa, Katsuyuki; Imai, Shinjiro; Kasuya, Kenji; Abe, Kimio; Adachi, Yu; Fukudome, Shin-ichi; Takahashi, Yoshimasa; Hachimura, Satoshi (PloS one, 2014)
The mucosal immune system provides the first line of defense against inhaled and ingested pathogenic microbacteria and viruses. This defense system, to a large extent, is mediated by the actions of secretory IgA. In this study, we screened 140 strains of lactic acid bacteria for induction of IgA production by murine Peyer's patch cells. We selected one strain and named it Lactobacillus plantarum AYA. We found that L. plantarum AYA-induced production of IL-6 in Peyer's patch dendritic cells, with this production promoting IgA(+) B cells to differentiate into IgA-secreting plasma cells. We also observed that oral administration of L. plantarum AYA in mice caused an increase in IgA production in the small intestine and lung. This production of IgA correlated strongly with protective ability, with the treated mice surviving longer than the control mice after lethal influenza virus infection. Our data therefore reveals a novel immunoregulatory role of the L. plantarum AYA strain which enhances mucosal IgA production and provides protection against respiratory influenza virus infection.